STRATEGI KEPEMIMPINAN KH. SALAHUDDIN WAHID DALAM MELAKUKAN TRANSFORMASI Di PESANTREN TEBUIRENG - Matnuri, Rizky Wahyu El-Fitri; Abdullah Aminuddin Aziz (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to reveal the leadership strategies implemented by KH Salahuddin Wahid in transforming the Tebuireng Islamic boarding school. Employing a qualitative approach with a case study method, this research analyzes various data sources such as documents, interviews, and observations. The findings indicate that KH Salahuddin Wahid applied innovative transformational leadership strategies in modernizing the Tebuireng boarding school without abandoning its traditional values. Several key strategies implemented include: (1) Human resource empowerment through improving the quality of education and training for students and educators. (2) Curriculum innovation by integrating modern science into religious learning. (3) Strengthening organizational governance with greater transparency and accountability. (4) Building networks of cooperation with various educational institutions and communities. These strategies have successfully brought about significant changes in the Tebuireng boarding school, including improved education quality, development of the boarding school's economy, and strengthening the role of the boarding school in society. This research makes a significant contribution to understanding the dynamics of transformational leadership in the context of Islamic boarding schools. The results of this study are expected to serve as a reference for other boarding school leaders in their efforts to modernize boarding schools without neglecting religious values.